2005
DOI: 10.1213/01.ane.0000159379.54705.84
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil as a Single Drug for Extracorporeal Shock Wave Lithotripsy: A Comparison of Infusion Doses in Terms of Analgesic Potency and Side Effects

Abstract: Remifentanil is an appropriate analgesic choice for patients undergoing extracorporeal shock wave lithotripsy (ESWL) therapy, as it has both fast onset and offset times. We studied remifentanil as a sole drug for ESWL and have shown that an infusion rate of 0.05 microg x kg-1 x min-1 plus patient-controlled analgesia demands of 10 microg provides adequate analgesia and has significantly less side effects than a dose of 0.1 microg x kg-1 x min-1 plus 10 microg demands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 19 publications
0
25
0
3
Order By: Relevance
“…[8] It has been shown that a lower basal remifentanil infusion rate decreases the side effects of treatment (nausea, vomiting, itching and dizziness) with no difference in VAS compared to a higher infusion rate. [9] A bolus delivery with no basal infusion dose may lead to a faster recovery with no change in patient comfort or overall satisfaction. [10] In our study, we did not administer a basal infusion and provided a bolus dose, with dose escalation as required.…”
Section: Discussionmentioning
confidence: 99%
“…[8] It has been shown that a lower basal remifentanil infusion rate decreases the side effects of treatment (nausea, vomiting, itching and dizziness) with no difference in VAS compared to a higher infusion rate. [9] A bolus delivery with no basal infusion dose may lead to a faster recovery with no change in patient comfort or overall satisfaction. [10] In our study, we did not administer a basal infusion and provided a bolus dose, with dose escalation as required.…”
Section: Discussionmentioning
confidence: 99%
“…No se recomienda su uso en embarazadas, durante la lactancia ni en menores de 2 años. Hasta en el 9% de los pacientes puede haber rigidez muscular, pero esta se reduce a 1% cuando se usa junto con un hipnótico potente o con un relajante muscular, esto en el escenario de la anestesia general o en el uso de infusión continua (34,39,41,42).…”
Section: Eficienciaunclassified
“…Es konnte gezeigt werden, dass die Verwendung von Remifentanil in niedriger Dosierung (bis 0,3 μg/kg-KG/min) eine ausreichende Analgesie bei Zahnextraktionen [20], Knochenmarkpunktionen [7], fiberoptischen Bronchoskopien [9], Endoskopien und Biopsien [36] bieten kann. Nach Abschluss der Intervention und der kontinuierlichen Remifentanilapplikation war in den genannten Studien in der Mehrheit der Fäl-le keine postoperative Schmerztherapie erforderlich [7,9,20,36,40]. Es kann jedoch nicht ausgeschlossen werden, dass es auch bei diagnostischen Untersuchungen oder Interventionen zu starken Schmerzen nach Beendigung einer Intervention kommen kann.…”
Section: Kurzeingriffe Und Diagnostische Untersuchungenunclassified